Quantitative Aspects of Employee Compensation - Hrachovcová, Johana; Chrobok, Viktor; Zouhar, Jan, 1982-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis explores the relationship between employee expenses and company performance in the Czech Republic, focusing on both financial costs and non-monetary benefits. While many existing studies examine how compensation affects individual motivation and productivity, fewer analyse how overall employee-related costs influence firm-level financial outcomes. Using a panel dataset of Czech firms' financial data from 2024 and manually collected data on non-financial perks, this study employs descriptive statistics, one-way ANOVA, and sector-level panel regression with robust standard errors. The results indicate that personnel costs generally correlate with profit per employee (PPE), return on assets (ROA), or return on equity (ROE) across most industry sectors, though the relationship is often nonlinear or lagged. The number of non-monetary benefits was not significantly associated with performance, underscoring the importance of tailored compensation strategies across different sectors. These results suggest that optimising personnel costs can enhance firm performance, rather than simply increasing expenditures. HR managers should consider sector-specific factors and long-term effects. This study provides insights into how compensation costs impact performance, offering valuable guidance for both researchers and practitioners.
Vedoucí práce: Viktor Chrobok
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonometrie a operační výzkum [obor dipl. práce]; diplomové práce; master's theses